(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Tawangsari and Mendoh Kidul hamlets are several hamlets located in the Semowo Village area, Pabelan District, Semarang Regency which have several potential resources that can be used as a support for the existence of a natural tourism village. Efforts to improve skills and management of these resources have been carried out through several series of training activities, including those related to increasing skills in utilizing digital platforms, village websites, while forms of assistance that have been carried out include improving website management and mapping some of the potential resources in the village area. Semowo. From several series of activities that have been carried out, efforts to pioneer the existence of tourist villages have begun to be directed to how to map the potential of existing resources in several hamlets in the Semowo Village area. The implementation of this training provides a practical overview of aspects of optimization village websites, especially in strengthening human resources in digital marketing / e-Marketing capacity or promoting nature tourism. The outputs of this activity are: 1) A village website that describes a map of Potential Areas for Development of Nature Tourism Villages; 2). MoU, cooperation between the village government and university leaders for assistance; 3) .Publication of community service activity programs on the web and social media